The (non)place of migration? The European Pillar of Social Rights and the representations of people with a migration background in Portugal - Marques, J. S.; Martinho, A. L.; Topa, J. (Social Inclusion, 2025)
Recognising migration as a defining feature of contemporary society and politics, this article critically uses the European Pillar of Social Rights (EPSR) as an analytical framework and examines how it relates to migration. Although migration is intrinsically linked to every dimension of the EPSR, we argue that it is largely absent from this framework. Moreover, while existing literature has explored various factors shaping public attitudes toward people with a migration background (PMB) and migration policies, little is known about how PMB represent these issues. Based on 73 semi‐structured interviews conducted in Porto, Portugal, this study fills that gap by analysing their perspectives on EPSR principles and on recent migration policy changes in the country, which have become less inclusive. Our findings show that framing migration as a crisis reinforces material and symbolic borders, which PMB simultaneously contest and internalise.